STATE AND LOCAL ANTI-DISCRIMINATION AND DISCRIMINATORY EMPLOYMENT PROPOSALS (Tufts Archival Research Center, 2007)
Report outlining anti-discrimination and discriminatory employment proposals at the state and local levels. Reports that anti-discrimination measures have passed in the following states: Colorado, Indiana, Kentucky, Mississippi, New Mexico, North Dakota, Oklahoma, Oregon, Rhode Island, South Carolina, South Dakota, Tennessee and Virginia. Lists by state current legislative activity regarding anti-discrimination proposals.